4 - Students perceiving risk: a quantitative assessment on three South African university campuses - Asta Rau,; Sarah Radloff,; Jan K. Coetzee,; Carlo Nardi,; Ria Smit,; Sethulego Z. Matebesi, (African Sociological Review, 2015)
This paper documents risk as perceived by students in three South African universities—it focuses on risk encountered in everyday choices such as sexual behaviour, alcohol use and freedom of association.The project originated in qualitative research conducted over two years (2008- 2009) among Rhodes University (RU) Sociology students. A second—quantitative—phase began in 2010 when findings from the initial phase were used to guide students in designing and piloting a questionnaire. Pilot results then informed a final research iteration in which a second questionnaire was designed and administered at three universities.The final questionnaire proved robust and performed very well. Among the 1694 valid cases included in analyses, strong associations were found between the universities, respondents’ sex and their worldview. Exploratory factor analysis revealed four latent constructs underlying all responses: The existential experience of risk; Stress and pressure resulting from exposure to financial and emotional risk; Risks attached to the everyday university culture; and Promiscuity. These constructs explained 59.8% of the total variance in all observed cases (all respondents in all universities). Students’ perception of risk in their lives is complex and multi-dimensional. The research found considerable evidence for Beck’s claim that in late modernity there is increasing individualisation in people’s perception of risk. Also, the degrees to which specific risks resonate in student consciousness demonstrate that risk is—as Zinn claims—both constructed and real.